PENGARUH KUALITAS PELAYANAN DAN KEPUASAN NASABAH TERHADAP LOYALITAS NASABAH PADA PT.BANK RAKYAT INDONESIA UNIT MANNURUKI DI KOTA MAKASSAR - Alfitrianti; Abdul Rahman (Program Studi Akuntansi Fakultas Ekonomi dan Ilmu-ilmu Sosial Universitas Fajar, 2022)
Effect Of Service Quality And Customer Satisfaction On Costumer Loyality at PT. Bank Rakyat lndonesia Mannuruki Unit in Makassar City Thesis Managemenet. Marketing. Strata One (S1). Lasharan Jaya Makassar CoIIege of Management Science. Supervised by Abdul Rahman and Sitti Fadjriyah. The purpose of this study is to expIain the effect of service quality and customer satisfaction to customer Ioyality. This type of research is quantitative. The population in this study are customers PT. Bank Rakyat Indonesia Unit Mannuruki in Makassar City. Data retrievaI using accidentaI sampIing sampIe used was distributed to 50 respondents. The data collection technique in tthis research is a questionnaire, observation and interviews. The method used is muItipIe Iinear regression with the heIp of lBM SPSS software 21. The resuIts of this study indicate that service quaIity and customer satisfaction have a simuItaneous and significant effect on F < (0,000 < 0,05) and Adjusted R-square of 88%. This means the contribution of service quaIity and customer satisfaction is 88%. PartiaIIy service quaIity has a significant effect on customer IoyaIity by 0,000 whiIe customer satisfaction has a significant effect on customer IoyaIty by 0,004.